Work Integrated Social Enterprises: Balancing social impact and economic sustainability through governance and policy support - Daniela Andrén; Anna Kremel (Örebro University School of Business, 2025)
Work Integrated Social Enterprises (WISEs) have emerged as a powerful and dynamic force in redefining the established norms while enhancing sustainability, promoting integration and nurturing more inclusive working societies by addressing employment barriers for marginalized groups. Using data from semi-structured interviews with WISEs in a mid-sized Swedish municipality, this article's findings reveal the challenges they face, such as financial sustainability, the need for formal organizational structures, and societal prejudices. The findings highlight WISEs' strategies for balancing economic stability with their social mission and emphasize the pivotal role of municipal and regional governance in supporting their operations. Targeted policy support in areas like management, human resources, and financial backing is essential to ensure WISEs' survival and long-term success.
Keywords: L31; I38; R58; 330; work integrated social enterprises; social inclusion; entrepreneurship; municipal support